MakeCode for Lego Mindstorms EV3 - Voštinár, Patrik (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Computer Science is nowadays very popular and requested in almost all companies. Many companies would like to have more IT professionals. Therefore we would like to motivate students from the beginning of their education to learn Computer Science, especially programming. There are many educational aids, which could be used for showing students, that programming is not so hard, as they think. The contribution describes our experience with using the online environment Microsoft MakeCode and the most popular educational robot Lego Mindstorms EV3 in an extracurricular activity for primary school children at Matej Bel University, Slovakia. In this paper, we present environment MakeCode and examples of tasks, which we are using for teaching programming in this environment.